Design of automatic food dosing and oxygenation for a carp recirculating aquaculture system (RAS) - Mohamed Aly, El-Messery Wael (Universidad Autónoma Chapingo, 2011)
During the past years the trend to move from conventional open systems to high density and highly productive recirculation aquaculture systems (RAS) was observed for its advantages. Recirculating aquaculture systems was poorly applied in Mexico, and the majority of its components were imported. The main objectives of the present study was to design and evaluate each component of a recirculating aquaculture system under local Mexican conditions, solids separator was evaluated obtaining optimum operations factors of water level in fish tank 90 cm and 2.54 cm of tank base diameter. Four suitable aerators locally designed for RAS was evaluated for choosing the máximum aeration efficiency (AAE). Spray column aerator records the highest AAE of 1.075 kgO2/kW hand oxygen transfer rate of 23.04 gO2/h. Tezontle (Volcanic sand) as an alternative media for the biostrata for its higher cost in biofilters was studied. Total ammonia nitrogen removal efficiency was 64.5 % and 73.4 % for the Tezontle and Bio-strata respectively, so the Tezontle can substitute the biostrata as an alternative media for the biofilter for its lower cost. The oxygen budgets in RAS was studied realizing one model to calculate aeration requirements and aerator size for whatever RAS producing mirror carp. Recirculating aquaculture system to preserve water; the total water used during the growing season to produce 18 kg/tank was 4666.55 liter of water. An automatic feeder was designed to provide predetermined amounts of food at controlled feeding times; food conveying was studied optimizing energy consumption.An intelligent instrumentation system monitoring and control three fish tanks with one galvanic dissolved oxygen probe and its transmitter. Peristaltic pumps extracted water from each tank without adding oxygen to the sample and dissolved oxygen measurements were auto-calibrated and statistically diagnosed.
Tesis (Doctorado en Ingeniería Agrícola y Uso Integral del Agua)
Keywords: Recirculating aquaculture system, automatic feeder, oxygenation, monitoring and control